2021
DOI: 10.1021/acssuschemeng.0c08462
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Process to Produce Ferromanganese and Direct Reduced Iron by Natural Gas

Abstract: The application of natural gas instead of solid carbon to produce ferromanganese is a way forward in sustainable development. Mass and energy balances for an integrated duplex process to produce ferromanganese and direct reduced iron (DRI) by natural gas were studied. The process consists of natural gas injection into molten ferromanganese yielding carbon and hydrogen in which the dissolved carbon into the molten metal bath reduces MnO from a coexisting molten slag that is produced from the smelting of mangane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…For instance, the energy consumption is the highest when FeMn is produced via the use of iron oxide in the charge of the PRR, and this is obvious as more hydrogen is needed compared to the other metal products according to Table 2. To evaluate the obtained energy consumption values, theoretical and industrial energy consumptions for HCFeMn production from high grade Mn ores in SAF [3,21] are also given in Figure 13. It is observed that the production of Green FeMn via HAlMan process is advantageous than the current SAF technology considering both theoretical and industrial cases.…”
Section: Energy Consumptionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, the energy consumption is the highest when FeMn is produced via the use of iron oxide in the charge of the PRR, and this is obvious as more hydrogen is needed compared to the other metal products according to Table 2. To evaluate the obtained energy consumption values, theoretical and industrial energy consumptions for HCFeMn production from high grade Mn ores in SAF [3,21] are also given in Figure 13. It is observed that the production of Green FeMn via HAlMan process is advantageous than the current SAF technology considering both theoretical and industrial cases.…”
Section: Energy Consumptionmentioning
confidence: 99%
“…The production of HCFeMn through a carbothermic process in SAF is accompanied with significant CO 2 emission and 1-1.4 tCO 2 /t metal. On the other hand, SAF process is an energy intensive process, and 2000-3000 kWh energy is utilized per ton metal as presented previously [3]. Therefore, the development of new sustainable Mn production processes is important to reduce the greenhouse gases in the future.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ey concluded that the reduction time should be appropriately extended to reduce surface defects of new iron particles, that the semi-wet ballmill process and DRI are not suitable for processing, and that the ideal one should be selected from other wet ball mills. Safarian [20] applied an integrated duplex process method to examine the mass and energy balances to produce ferromanganese and directly reduced iron (DRI) with natural gas. He concluded that the production of ferromanganese and DRI with natural gas is feasible in terms of process chemistry in a FeMn reactor and causes 40% less CO2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%